Purchase of drugs in non-pharmacy outlet in the aspect of patient's safety - Ewelina Zelek; Maja Wiśniewska; Jagoda Pasternak; Artur Beberok; Dorota Małgorzata Wrześniok (Polish Pharmaceutical Society, 2021)
SUBJECT OF STUDY: Currently, more and more people are choosing to buy medicines in places other than the pharmacy. The storage conditions of drugs being sold outside the pharmacy often differs from the norms and pharmacy rules, and exposing drugs to sunlight radiation and high temperature may lead to changes in the composition of the drug and affect the safety and efficacy of pharmacotherapy. The COVID-19 epidemic fundamentally emphasized the role of pharmacists, initiating the full use of their potential which support the resources of an overburdened healthcare system. The role of pharmacies in the crisis of the current global pandemic situation is crucial as they are often the only point of contact with healthcare professionals for patients who need reliable information. PURPOSE OF RESEARCH: The aim of the study was to determine where patients most often buy medicines and whether they are aware of the dangers connected with the use of medicines purchased in non-pharmacy-outlet. MATERIAL AND METHODS: The questionnaire consisted of 27 original questions. The survey was completely anonymous and 251 people took part in the study. The vast majority of the respondents were women and people declaring non-medical education. RESULTS: The obtained results indicate that the respondents do not trust people selling drugs without medical education. However, despite the important role of healthcare and information provided by pharmacists, over 70% of respondents buy medicines outside the pharmacy. 54.8% of respondents are aware of the quality control of drugs in pharmacies (withholding or recalling procedure), as well as insufficient control at other drug sale points. A positive phenomenon is the fact that over 89% of patients choose to buy drugs in a pharmacy in case of emergency. Moreover, more than 72% of users are aware that improper storage of drugs can change their composition and cause undesirable effects. CONCLUSIONS: The conducted study pointed the need for health education of patients. It is necessary to provide patients with the address to buy drugs where they are properly stored and sold by a qualified team of pharmacists. This indicates the need to implement and develop Pharmaceutical Care in Poland.